Formulation Design of Fast Dissolving Tablets of Fexofenadine Hydrochloride by Sublimation Method - Nagendra Kumar D; Raju SA; Shirsand SB (International Journal of Pharma and Bio Sciences, 2010)
In the present work, fast dissolving tablets of fexofenadine hydrochloride were designed with a view to enhance patient compliance by sublimation method. In this method, camphor was used as the subliming agent (upto 30% w/w), crospovidone and croscarmellose sodium (2-8% w/w) were used as super-disintegrants. Estimation of fexofenadine hydrochloride in the prepared tablet formulations was carried out by extracting the drug with methanol and measuring the absorbance at 259 nm. The prepared formulations were further evaluated for hardness, friability, drug content uniformity, in vitro dispersion time, wetting time and water absorption ratio,. Based on in vitro dispersion time (approximately 5-14 sec), two promising formulations (one from each super-disintegrant) were tested for in vitro drug release pattern in pH 6.8 phosphate buffer and short-term stability (at 40ºC/ 75% RH for 3 months) and drug-excipient interaction (IR spectroscopy) were studied. Among the two promising formulations, the formulation (SCP3) containing 8% w/w of crospovidone and 30% w/w camphor as the subliming agent emerged as the overall best formulation (t50%4.3 min) based on drug release characteristics in pH 6.8 phosphate buffer compared to commercial conventional tablet formulation (t50%15 min). Short-term stability studies on the promising formulations indicated that there are no significant changes in drug content and in vitro dispersion time (p<0.05).